Essential oils of Marrubium L. taxa from aegian province of Turkey. Issue 6 (1st November 2020) - Demiroz Akbulut, T.; Demirci, B.; Baykan, S.
ABSTRACT: A comparative study on the essential oil (EO) compositions of seven Marrubium taxa from nine locations in Aegean province of Turkey was performed by this study. The essential oils analysed by gas chromatography (GC) and gas chromatography-mass spectroscopy (GC-MS). The major compounds of all species were detected as sesquiterpenes; ( Z)-β- farnesene, germacrene D, β- caryophyllene, caryophyllene oxide and bicyclogermacrene in variable rates for different taxa. Moreover, this is the first study on EO composition of endemic M. rotundifolium Boiss. and chemical variabilities of the EOs of other Marrubium taxa collected from Turkey.